라미부딘 내성 만성 B형 간염 환자에 있어 라미부딘과 아데포비어 병용 요법의 치료 효과와 특성 분석 - 김동훈 (The Graduate School, Ajou University, 2012)
Background: Add on adefovir (ADV) to ongoing lamivudine (LAM) is an established treatment modality for treatment of LAM resistance with chronic hepatitis B. We assessed the long?term efficacy (median follow-up of 20.18 months) of ADV add-on LAM therapy in 89 LAM-resistant patients. Methods: 89 patients (29.2% cirrhotics, 76.4% hepatitis B e antigen positive) with LAM resistant patients who were not experienced ADV monotherapy were enrolled, retrospectively from August 2005 to October 2010. All the patients were treated with ADV add-on LAM therapy. Liver function test, hepatitis B virus (HBV) DNA and HBeAg/HBeAb were assessed every 3 months. ADV associated (rtA181T/V and rtN236T) mutations were looked for at intervals in all HBV DNA-positive serum samples, yearly Results: Cumulative ratio of undetectable HBV DNA level (<50 copies/mL or <8.6 IU/mL) at 6 months, 1 year, and 2 years were 15.7%/44.2%/45.4% for HBeAg positive group and 34.8%/39.1%/52.6% in HBeAg negative group. Seroconversion was observed 10.2%/19.7%/23.6% in 6 months, 1 year, and 2 years. Virologic breakthrough phenomenon was seen 1.1%. Conclusions: LAM and ADV combination therapy effectively suppresses HBV replication and prevents virologic and clinical breakthrough in LMV-resistant patients. And emergence of ADV-resistant mutants is rare, at least over a period of 24 months.
학위논문(석사)아주대학교 일반대학원 :의학과,2012. 2
Keywords: 만성 B형 간염; 라미부딘 내성; 아데포비어; 바이러스 돌파